Perubahan karakteristik fisikokimia dan mikrobiologi ketupat selama penyimpanan suhu dingin [Changes on physicochemical and microbiological characteristics of ketupat during storage at cold temperature] - Isnaini Rahmadi; Sugiyono Sugiyono; Nugraha Edhi Suyatma (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
Ketupat is an Indonesian indigenous food made from rice which is wrapped by young coconut leaves and cooked into the boiling water. Storage temperatures might affect the physicochemical and microbiological characteristics of ketupat. The objective of this research was to observe the effect of 2 rice varieties with different amylose content and the percentage of ketupat filling on the change of physicochemical and microbiological characteristics of ketupat during storage at cold temperature (T= 5 oC; RH= 19,2 %). Ketupat was produced by using two rice varieties, namely IR 64 and Pandan Wangi. The percentage of ketupat filling resulted in higher ketupat hardness during storage. In addition, the hardness of ketupat increased during storage. The percentages of ketupat filling did not affect pH and aw of the ketupat during storage; however, the higher the percentages of ketupat filling resulted in the lower water content. The water content and pH did not change during storage. Ketupat stored at cold temperature was able to maintain the microbiological quality until the 9th day.